2020
DOI: 10.1183/23120541.00542-2020
|View full text |Cite
|
Sign up to set email alerts
|

Persistent symptoms 3 months after a SARS-CoV-2 infection: the post-COVID-19 syndrome?

Abstract: BackgroundMany patients with COVID-19 do not require hospitalisation, let alone have undergone COVID-19 testing. There is anecdotal evidence that patients with “mild” COVID-19 may complain about persistent symptoms, even weeks after the infection. This suggests that symptoms during the infection may not resolve spontaneously. The objective of this study was to assess whether multiple relevant symptoms recover following the onset of symptoms in hospitalised and non-hospitalised patients with COVID-19.Methods211… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

53
631
5
58

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 711 publications
(809 citation statements)
references
References 23 publications
53
631
5
58
Order By: Relevance
“…There is some evidence for prolonged fatigue for non-hospitalised patients in the months after being diagnosed with COVID-19. 3 The current study not only shows that other aspects of health are also affected in these subjects, but compared to the general population, social functioning and general health were the most affected, as shown by z-scores. Moreover, differences from RAND-36 population norms were most apparent for dimensions associated with aspects of mental health, which in addition to social functioning, included role-limitations due to emotional problems and emotional well-being.…”
supporting
confidence: 47%
See 1 more Smart Citation
“…There is some evidence for prolonged fatigue for non-hospitalised patients in the months after being diagnosed with COVID-19. 3 The current study not only shows that other aspects of health are also affected in these subjects, but compared to the general population, social functioning and general health were the most affected, as shown by z-scores. Moreover, differences from RAND-36 population norms were most apparent for dimensions associated with aspects of mental health, which in addition to social functioning, included role-limitations due to emotional problems and emotional well-being.…”
supporting
confidence: 47%
“… 1 There is less evidence for the non-hospitalised, but breathlessness and fatigue is common after several months. 3 , 4…”
mentioning
confidence: 99%
“…These findings extend recent studies which have argued for a high prevalence of Post-COVID clinical manifestation and claimed that long term consequences of COVID-19 involve both central and peripheral nervous systems 1,2,10,11 . In particular, Goertz and coauthors 5 (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical findings on previously hospitalised and non-hospitalised patients with COVID19 reported the persistence of multiple symptoms, particularly fatigue and dyspnoea 4 . Accordingly, some authors have suggested the so called, but not yet defined, "post-COVID-19 syndrome" based on symptoms reported after three months of SARS-CoV-2 infection 5 . Few follow up studies, however, have investigated patients discharged from hospital after recovery from COVID-19 and no data about persistent neurological manifestations are available yet.…”
Section: Introductionmentioning
confidence: 99%
“…Even though both validated and standardized generic and respiratory-specific quality of life questionnaires exist, the question remains which instrument is more adequate in patients with a new disease such as COVID- 19. As pulmonary function may be impaired [8,9] and dyspnea is one of the most prevalent symptoms in patients with COVID-19 [3], it seems reasonable to hypothesize that the impact on respiratory-specific quality of life, which not only focuses on the state of the airways but also on the patients' functional needs, is very prominent in these patients. Therefore, our objective was to assess respiratory-specific quality of life in addition to generic quality of life in non-hospitalized patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%